Sustainability of products, processes and supply chains : theory and applications - You, Fengqi (Amsterdam : Elsevier, 2015)
Sustainability of Products, Processes and Supply Chains: Theory and Applications presents the recent theoretical developments and applications on the interface between sustainability and process systems engineering. It offers a platform for cutting-edge, holistic analyses of key challenges associated with computer-aided tools for incorporating sustainability principles and approaches into the design and operations of multi-scale process systems, ranging from molecular and products systems, to energy and chemical processes, and supply chains. Presents recent theoretical developments and appli.
6.5 REGULATION OF OSCILLATORY PHENOMENA6.6 OPERATING CONDITION OPTIMIZATION; 6.7 DISCUSSION; 6.8 CONCLUSION; APPENDIX; NOMENCLATURE; Acknowledgments; REFERENCES; Part II -- Carbon capture, utilization and sequestration; Chapter 7 -- Sustainable Process Design: Sustainable Process Networks for Carbon Dioxide Conversion; 7.1 INTRODUCTION; 7.2 IDENTIFYING MORE SUSTAINABLE DESIGNS; 7.3 METHOD AND TOOLS; 7.4 MORE SUSTAINABLE CO2 CONVERSION PROCESS DESIGNS; 7.5 CONCLUSIONS; REFERENCES; Chapter 8 -- Pressure Swing Adsorption Optimization Strategies for CO2 Capture; 8.1 INTRODUCTION
Includes bibliographical references and index.
Online resource; title from PDF title page (Ebsco, viewed May 8, 2015).
Elsevier
Keywords: Sustainable engineering; Sustainable design; TECHNOLOGY & ENGINEERING / Environmental / General; Business logistics -- Environmental aspects; Business logistics; Sustainability; Sustainable design; Sustainable engineering; Electronic books